EDUCATIONAL INTERVENTION DIGITAL FINANCE ON THE SUSTAINABILITY OF CREATIVE ECONOMY MSMEs - Mahadi, Nur Rizky Putri; Maintji, Mohamad Rizki; Hidayah, Magfira Nurul; Haju, Fadel (LP2M Universitas Bina Mandiri Gorontalo, 2025)
This study examines the effectiveness of digital financial education interventions in improving the sustainability of Micro, Small, and Medium Enterprises (MSMEs) in the creative economy sector. MSMEs, as pillars of the national economy, often face challenges in financial management and digital technology adaptation. Digital financial education is crucial for equipping MSMEs with the knowledge and skills needed to utilize digital financial instruments, manage risks, and make sound financial decisions. The research method employs a qualitative approach with a comprehensive literature review of accredited national journals. The analysis results indicate that digital financial education interventions significantly contribute to improving MSME financial literacy, financial technology adoption, operational efficiency, and ultimately, business sustainability. Structured and continuous education, tailored to the characteristics of creative economy MSMEs, can drive innovation and competitiveness in the digital era. The practical implications of this research are recommendations for policymakers and related institutions to design inclusive and relevant digital financial education programs to support the growth of creative economy MSMEs.